N-butylparaben exposure during perinatal period impairs fertility of the F1 generation female rats. (December 2018) - Maske, Priyanka; Dighe, Vikas; Vanage, Geeta
Abstract: Parabens are a class of preservatives widely used in the majority of personal care products, cosmetics, medicines, and food products. However, current literature suggests its plausible role as an endocrine disruptor, hence the present study was undertaken to delineate the effects of n-butyl paraben on perinatally exposed F1 female rats. F0 dams were exposed subcutaneously to n-butylparaben from gestation day 6 (GD 6) to postnatal day (PND) 21 with doses of 10, 100, and 1000 mg/kg Bw/day in corn oil. The F1 female rats were monitored for pubertal development and sexual maturation through PND 30, 45, and 75; which were subsequently subjected to fertility assessment at PND 75. Perinatal exposure to n-butylparaben resulted in- a. Delayed age of vaginal opening with disturbed estrus cycle in F1 female rats. b. A significant reduction in fertility with increased pre-and post-implantation loss; impaired steroidogenesis with decreased estradiol, progesterone, and increased testosterone levels. c. An impairment in folliculogenesis with increased number of primordial follicle maturation and reduced number of corpora leutea (CL). The morphological analysis showed degenerated follicles in the ovaries and inadequate development of the myometrium in the uterus. d. Perturbed expression levels of estrogen receptors alpha (ER α), beta (ER β) and Steroidogenic acute regulatory gene (StAR) in the ovary at PND 75. This study documents impaired steroidogenesis and folliculogenesis might be the prime reason for the reduced fertility of F1 female rats. Hence, our study suggests that health monitors need to counsel potential females planning for pregnancy to avoid exposure to parabens. Highlights: n-butylparaben exposure delayed vaginal opening as well decreased estrus cycle length in F1 female rats. Impaired steroidogenesis and folliculogenesis in F1 female rats upon perinatal exposure to n-butylparaben. Increased expression of ERα, ERβ, and StAR in the ovaries at PND 75 of adult F1 female rats. Subfertility with increased pre- and post-implantation loss in the F1 females exposed to n-butylparaben. Inadequate development of myometrium in F1 females exposed perinatally to n-butylparaben.